2013
DOI: 10.1590/s2237-60892013000200002
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the prevalence of bipolar disorder and bipolar spectrum disorders in population-based studies

Abstract: This paper describes the findings of a systematic literature review aimed at providing an overview of the lifetime prevalence of bipolar disorder and bipolar spectrum disorders in population-based studies. Databases MEDLINE, ProQuest, Psychnet, and Web of Science were browsed for papers published in English between 1999 and May 2012 using the following search string: bipolar disorders OR bipolar spectrum disorders AND prevalence OR cross-sectional OR epidemiology AND population-based OR non-clinical OR communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 45 publications
1
20
0
3
Order By: Relevance
“…Although systematic reviews on the prevalence of BD have been previously published, 14,16,17 we have not identified studies that have statistically treated their findings through meta-analysis. This is important, since the meta-analytic approach can yield more reliable prevalence estimates, in particular for conditions with low prevalence, such as BD.…”
Section: Introductionmentioning
confidence: 99%
“…Although systematic reviews on the prevalence of BD have been previously published, 14,16,17 we have not identified studies that have statistically treated their findings through meta-analysis. This is important, since the meta-analytic approach can yield more reliable prevalence estimates, in particular for conditions with low prevalence, such as BD.…”
Section: Introductionmentioning
confidence: 99%
“…This condition does not only affect the mood of patients, but also their activity levels, energy and fear-danger notions, and leads to social and biological damages causing disability of performing quotidian activities. BD is among the 10 most disabling illnesses in the world, and it is estimated that 2-15% of the worldwide population is affected by one of its types or subtypes (Dell'Aglio et al, 2013). The bipolar spectrum recently described by the Diagnostic and Statistical Manual of Mental Disorders, (American Psychiatric Association, 2013), indicates a large scale of mood patterns, thereby allowing the possibility of diagnosing pathology (Figure 1).…”
Section: Bipolar Disordermentioning
confidence: 99%
“…2,3 It is worth pointing out that these might be underestimates because, compared to longitudinal studies, data from population-based cross-sectional studies may underestimate the real prevalence of BD. 4 More importantly, the authors found an increase in prevalence estimates over recent decades, in parallel with changing DSM diagnostic criteria. Lifetime prevalence of BD type I has virtually doubled with each edition from DSM-III to DSM-IV.…”
mentioning
confidence: 94%